The Formation of Connection between Urmia Lake Basin and East Anatolia Ali Binandeh - Ali Binandeh (مجله مطالعات ایرانی, 2018)
Urmia Lake Basin with its special natural and geographical conditions has always attracted the attention of different groups of people from prehistory to the present. The connection of Urmia Lake basin with North Mesopotamia by corridors like Kel-e Shin and Haj Omran is much easier than the its connection with other regions, specially with central Zagros. Some see the formation of this connection a result of the migration of people in North Mesopotamia to this region, seeking better pastures and conditions through the valleys connecting the western part of Urmia Lake basin to North Iraq. According to archaeological evidences, during the Chalcolithic period, the connection between North-West Iran and East  Anatolia had been formed by Erzurum, the east of Aras river, and the periphery of Urmia Lake. Although in the discussion of cultural similarities, the evolution process of societies must be also taken into account, the evidences and records suggest that this culture is much more influenced by Mesopotamia and has been transferred through Zagros valleys.